2014
DOI: 10.1007/s12010-013-0718-9
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Sulfide and Production of Methane from Carbon Dioxide in Microbial Fuel Cells–Microbial Electrolysis Cell (MFCs–MEC) Coupled System

Abstract: Removal of sulfide and production of methane from carbon dioxide in microbial electrolysis cells (MECs) at the applied voltage of 0.7 V was achieved using sulfide and organic compound as electron donors. The removal rate of sulfide was 72 % and the Faraday efficiency of methane formation was 57 % within 70 h of operation. Microbial fuel cell (MFCs) can be connected in series to supply power and drive the reaction in MECs. Removal of sulfide and production of methane from carbon dioxide in MFCs-MEC coupled syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…Siegert et al reported higher methane yields in biocathodes when hydrogenotrophic methanogens where presented in the inoculum [73]. In agreement with other studies [44,45,55], these findings suggest that the presence of Archaea of the hydrogenotrophic genera Methanobacterium and Methanobrevibacter are crucial to produce methane in BESs and their presence in the inoculum favours electromethanogenesis processes. Obviously methanogens must be included in a wide range of inoculum, but also the presence of effective electron uptake species will ensure a free electron flow from the electrode to electromethanogens unable to attach on the electrode surface.…”
Section: Current Limitations In Electromethanogenesis and Proposedsupporting
confidence: 83%
See 2 more Smart Citations
“…Siegert et al reported higher methane yields in biocathodes when hydrogenotrophic methanogens where presented in the inoculum [73]. In agreement with other studies [44,45,55], these findings suggest that the presence of Archaea of the hydrogenotrophic genera Methanobacterium and Methanobrevibacter are crucial to produce methane in BESs and their presence in the inoculum favours electromethanogenesis processes. Obviously methanogens must be included in a wide range of inoculum, but also the presence of effective electron uptake species will ensure a free electron flow from the electrode to electromethanogens unable to attach on the electrode surface.…”
Section: Current Limitations In Electromethanogenesis and Proposedsupporting
confidence: 83%
“…In addition, methanogens have been found the main microbial community for the reduction of CO 2 into CH 4 in BES (Figure 3: reactions 1 and 6) [8,11,13,19,42,43]. Among such community, hydrogenotrophic methanogens (i.e., Methanobacterium or Methanobrevibacter ) have been found to play a main role (Figure 3: reaction 6) [19,44], specifically in studies dealing with mixed culture biocathodes in BESs [45]. Therefore favorable conditions for the growth and the activity of hydrogenotrophic methanogens, such as better bioavailability of H 2 , might lead to an increase in methane production by these systems.…”
Section: Electromethanogenesis Pathways Microbial Communities Andmentioning
confidence: 99%
See 1 more Smart Citation
“…6 All other reports on non-thermophilic MECs have identified Methanobacterium or Methanobrevibacter as the predominant archaea. 16,17 Other, less abundant methanogens identified in these MECs were Methanocorpusculum, Methanosarcina and Methanoculleus species. 17,18 The materials, [19][20][21] surface area, 22 and set cathode potentials 20 are known to affect abiotic rates of hydrogen gas production, and it is unclear to what extent these reactor materials or operational conditions contribute to the enrichment of hydrogenotrophic methanogens.…”
Section: Introductionmentioning
confidence: 99%
“…In sulfide-driven MES, the electricity required for MES is generated by the abiotic oxidation of the toxic contaminant sulfide to sulfur and the subsequent biological oxidation of sulfur to sulfate (Gong et al, 2013). A similar process has also been developed to supply electrons for the electroproduction of methane from CO 2 (Jiang et al, 2014). Moreover, MES and electromethanogenesis have been conducted in parallel with the biorecovery of cobalt at the cathode further illustrating the versatility of this technology (Huang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%